Desenvolvimento de nanocápsulas poliméricas contendo Indol-3-Carbinol e avaliação biológica das formulações - Gehrcke, Mailine (2016)
Indole-3carbinol (I3C) is a phytochemical that has several therapeutic properties. However, it is unstable against acid and light conditions. In this sense, polymeric nanocapsules are interesting alternatives for the encapsulation of this compound. Thus, this study aimed the nanocapsule suspensions development from poly(ε-caprolactone) or Eudragit® RS 100 and from medium chain triglycerides or rose hip oil. All the formulations showed adequate physicochemical characteristics with encapsulation efficiency around 40 % regardless of the used constituents. Furthermore, it was found that the nanocapsules increased about fourfold the compound photostability against UVC radiation, which was 10 % more effective for rose hip oil nanocapsules. The in vitro release profile studies demonstrated a biphasic release profile of I3C from nanocapsules, which is driven by Fickian diffusion. In biological evaluations of the formulations, they were divided in two groups: The first group consisted of nanocapsule suspensions prepared with poly(ε-caprolactone), intending to intravenous administration of I3C. In hemolysis test the formulations demonstrated hemocompatibility at 10 μg/ml. The DPPH scavenging activity assay showed that medium chain triglycerides nanocapsules and rose hip oil nanocapsules increased the I3C activity from 50 % to 72 and 81 %, respectively, demonstrating that rose hip oil nanocapsules are promising formulations. Thus, the antitumor activity of these suspensions was evaluated against breast tumor and glioma cells. The results demonstrated that nanoencapsulated I3C presented an antitumor effect two times higher than free I3C without causing cytotoxicity on astrocyte cells. The second group, which consisted of nanocapsule formulations prepared with Eudragit® RS 100 and rose hip oil, was evaluated in vivo concerning its antinociceptive action. The results showed that free I3C and nanocapsules had an onset of action at 30 min. However, free I3C has rapidly lost its effect, whereas nanocapsules prolonged the antinociceptive action of this compound until 6h. This way, the developed nanocapsules are promising alternatives for I3C administration in the control of cancer and pain treatment.